Optimizing tea waste as a sustainable substrate for oyster mushroom (Pleurotus ostreatus) cultivation: a comprehensive study on biological efficiency and nutritional aspect - Ahmed, Raisa; Niloy, Md. Asif Hasan Mazumder; Islam, Md. Shafiqul; Reza, Md. Selim; Yesmin, Sabina; Rasul, Shahriar Bin; Khandakar, Jebunnahar (Frontiers in Sustainable Food Systems, 2024)
In Bangladesh, rice straw (RS) and sawdust (SD) substrates have traditionally been used in the production of oyster mushrooms (Pleurotus ostreatus). However, the rising costs of these substrates have led many to look for alternatives. The present study thus focuses on the potential of waste tea leaves (WTL) for mushroom farming. We prepared various substrate mixtures by combining WTL with SD and RS, subsequently evaluating mushroom yield and various quality parameters such as amino acid concentration, mineral content, and biological efficiency. Our investigation revealed that WTL alone is not a suitable substrate for mushroom (Pleurotus ostreatus) growth. However, when combined with SD at a 50% ratio, it significantly boosts mushroom yield and biological efficiency (BE). Conversely, a reduction in yield was noted when WTL was mixed with RS in all tested treatments, although BE surpassed 50%. In summary, incorporating WTL into both substrates proves economically viable from the BE standpoint. According to PCA analysis, the minerals and amino acid content varied based on the different substrate formulations involving WTL blending with both SD and RS at different ratios. Remarkably, mushroom fruiting bodies exhibited lower levels of Na and Fe despite these elements being present in higher concentrations in the growing substrates, suggesting the inability of P. ostreatus to bioaccumulate Na and Fe. Conversely, we observed higher bioaccumulation of Zn and P, even exceeding substrate levels. Importantly, our findings showed that mushrooms cultivated on WTL-based formulations consistently contained elevated Zn levels irrespective of substrate types, indicating that WTL enriched Zn in mushrooms. Additionally, the Fe level increased specifically in RS +WTL-based formulations. All essential and non-essential amino acids were detected, with the highest concentration of histidine, isoleucine, and methionine found in the WTL + SD formulation. Non-essential amino acids (NEAA) like alanine and glutamic acid were more prominent in formulations combining WTL with RS. This study represents the first documented exploration of the impact of WTL on the accumulation of intracellular metabolites including minerals and amino acids, in P. ostreatus.